Bibliometric Study of Articles on Computational Thinking in Learning - Viviana Putri; Syahmani Syahmani; Yogo Dwi Prasetyo (Universitas Lambung Mangkurat, 2023)
One of the fundamental concepts for the high-level problem-solving abilities required by humans in the twenty-first century is computational thinking. The basic principles and ideas found in informatics and computer science are used to solve issues computationally with the help of computational thinking. The bibliometric examination of the research on computational thinking in learning is explained in detail in this article. Using the Scopus database and the Publish or Perish (PoP) program, articles were found. According to the search and sorting results, 187 of the 200 items were located between 2019 and 2022. The Mendeley Desktop program was used to alter the chosen metadata. The VOSviewer program is then used to evaluate further and display the modifications. Most articles published in the 2019â€“2022 timeframe with the keyword of computational thinking have been quoted quite a bit.Â